Female Coffee Lovers' Consumptive Lifstyle at Espresso Beach Cafe in Pariaman - Akdila Bulanov; Heru Permana Putra (HUMANISMA : Journal of Gender Studies, 2022)
This research was entitled Female Coffee Lovers' Consumptive Lifestyle at Espresso Beach Café in Pariaman. This study was a kind of illustrative subjective exploration that highlighted field research and did not put aside the concentration of writing that intended to describe the impolite behavior of female coffee lovers at Espresso Beach Café in Pariaman. The investigation strategy used in this research was purposive investigation. The informants taken in this study were female coffee lovers at Espresso Beach Cafe in Pariaman.The techniques used for collecting data were interviews, observations, and documentation. The results of this research showed that the quality of female coffee lovers was observed from their lifestyle and their public activities that spent a lot of energy with their friends. The inspiration for female coffee lovers was to satisfy their desires, supported by financial assistance and close friends that made female coffee lovers feel more comfortable in their exercise. The spendthrift behavior of female coffee lovers was in choosing the place, the type of the drink, the friends, friends’ nicknames, time according to their assumptions, how to drink a drink, visit, and the environment while drinking and saving pocket money.Kajian ini merupakan semacam eksplorasi subjektif ilustratif yang menyoroti tentang “Gaya Hidup Konsumtif Wanita di Espresso Beach Cafe Pariaman”, penelitian ini tidak mengesampingkan konsentrasi penulisan yang bermaksud menggambarkan cara tidak sopan perilaku para wanita pecinta kopi di Espresso Beach Café Pariaman. Strategi pengumpulan data yang digunakan dalam kajian ini menggunakan purposive samppling. Lokasi yang diambil dalam penelitian ini adalah para wanita di Espresso Beach Café Pariaman yang mendapat kesempatan untuk mengkonsumsi kopi. Strategi pengumpulan informasi yang digunakan adalah wawancara, observasi dan dokumentasi. Hasil penelitian ini menunjukkan bahwa kualitas yang dimiliki wanita yang menyukai kopi terlihat dari gaya hidup dan aktivitas publik mereka, menghabiskan banyak energi dengan teman-teman mereka. Inspirasi bagi para ahli kopi wanita adalah untuk memuaskan hasrat mereka, didukung oleh bantuan keuangan dan pasangan yang membuat para pecinta kopi wanita lebih nyaman dalam latihan penggunaan mereka. Perilaku boros yang dilakukan para wanita penikmat kopi adalah dengan memilih tempat coffeshope, jenis minuman, memilih teman minum kopi, waktu untuk nongkrong, cara meminum, dan berusaha menghemat uang saku.